Collecting Fragmentary Authors in a Digital Library (Greek Fragmentary Historians) - Berti, Monica; Romanello, Matteo; Babeu, Alison; Crane, Gregory (Tufts Archival Research Center, 2005)
This paper discusses new work to represent, in a digital library of classical sources, authors whose works themselves are lost and who survive only where surviving authors quote, paraphrase or allude to them. It describes initial works from a digital collection of such fragmentary authors designed not only to capture but to extend the ontologies that traditional scholarship has developed over generations: the aim is representing every nuance of print conventions while using the capabilities of digital libraries to extend our ability to identify fragments, to represent what we have identified, and to render the results of that work intellectually and physically more accessible than was possible in print culture.